Aplikasi Karagenan Sebagai Emulsifier Pada Sosis Segar Ikan Nila Merah (Oreochromis niloticus) - Putra, Aditya Cahya; Ibrahim, Ratna; anggo, apri dwi (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
One function is to carrageenan as emulsifier to improve the stability of the emulsion on the sausage.The purpose of this study was to determine the effect of the addition of carrageenan as an emulsifierwith different percentages of the quality of sausage as well as finding the best percentage ofcarrageenan were added in the process of making sausage. The benefits of this research is to provideinformation about the percentage of carrageenan for the best quality. The materials used are tilapiaand carrageenan. This research is experimental laboratories. Experimental design used wasRandomized Block Design with four treatments, the dough sausage without the addition ofcarrageenan 0% (control), batter sausage with the addition of carrageenan 3.5%, 4,0%, 4,5%. Thevariables measured were emulsion stability, gel strength, hedonic, moisture content, protein contentand fat content. Data were analyzed with parametric tests of variance and Data Real Honest. As forthe hedonic test using Kruskall Wallis test followed by Multiple Comparison Test. The results showedthat the addition of carrageenan to the sausage mixture causes the average value of emulsion stability,gel strength, hedonic, protein content and higher fat content is very noticeable compared to thesausage without the additionof carrageenan. The addition of 4% carrageenan in sausage batter tilapiaproduced the best emulsion stability (84.92%), gel strength (2871.93 gfcm), moisture content(70.05%), protein content (25.84%), fat content (16.51%) and the hedonic value of > 7,0 (preferablypanelists).